Hubungan Diabetes Melitus, Kolesterol dengan Skor Kalsium pada Pasien Hipertensi dengan Status Gizi Obesitas: Correlation between Diabetes Mellitus Type 2, Cholesterol with Calcium Score in Patient with Hypertension and Obesity - Saskia Dyah Handari; Mirna Rahmasari; Yurike Dhika Adhela (Universitas Airlangga, 2023)
Background: Obesity is more of a nutritional problem that becomes one of the double nutritional problems that must be overcome. A person with obesity tends to have a higher risk of developing hypertension, diabetes mellitus type 2, and the possibility of having a heart attack, which can show calcium scores in the heart. Objectives: This research aimed to analyze the relationship and look at differences in the incidence of DM type 2, cholesterol, and calcium scores in patients suffering from hypertension and obesity. Methods: This research used a cross-sectional study design with a quantitative method. The data collection was conducted at Siloam Hospital Surabaya (2018-2021). The determination of the sample adjusts to the criteria set by the researcher. Sample withdrawal used the purposive sampling method. The sample number was 59 men and 59 women. Research instruments were a questionnaire, interview, collecting data anthropometry, hypertension history, and cholesterol history. Results: Most of the subjects were elderly (38.1%). There were differences in the cholesterol history of women and man subjects (p=0.002). There was no noticeable difference in the history of DM type 2 in the subjects (p=0.092). There was no noticeable difference in calcium scores in the subjects (p=0.062). Most subjects other than having DM type 2 also had a history of cholesterol (73.3%). There was no noticeable correlation between cholesterol with DM type 2 in subjects (p=0.006). Most subjects with a history of DM type 2 was in a meaningful calcium score (26.6%). No association between DM type 2 and calcium score in subjects (p=0.102). Conclusions: There was no association between the incidence of diabetes mellitus type 2 and cholesterol and the incidence of DM type 2 with calcium scores in patients. There was a noticeable difference in the incidence of cholesterol in the subjects. No difference in the incidence of DM type 2 and calcium scores was found in subjects who were patients with a history of hypertension and obesity.